2014
DOI: 10.5935/1981-2965.20140137
|View full text |Cite
|
Sign up to set email alerts
|

Association of the tratament conventional and acupuncture in wound treatment on a Toucan. A case report

Abstract: _________________________________________________________________________________________________________________Resumo: Ainda hoje há um grande número de animais silvestres que sofrem de maus tratos oriundos do tráfico, sendo mantidos em cativeiros inadequados, sofrem com os atropelamentos nas estradas e são vítimas também de doenças infecciosas, por isso que a medicina de animais silvestres vem crescendo nos últimos anos. Por perceber que são poucos os trabalhos que relatam tratamentos executados em animais … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Regardless of the abundant reports on the effect of acupuncture on domestic or experimental animals and humans, reports involving wild animals are rare [4][5][6][34][35][36][37]. Acupuncture is also not often described in birds and is mainly published as meeting abstracts and in a few case reports [7][8][9][10]38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the abundant reports on the effect of acupuncture on domestic or experimental animals and humans, reports involving wild animals are rare [4][5][6][34][35][36][37]. Acupuncture is also not often described in birds and is mainly published as meeting abstracts and in a few case reports [7][8][9][10]38].…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture is a noninvasive and safe treatment option, as well as a widely accepted technique for alleviating pain and inflammation. Reports on domestic animals and, recently, in south tortoises, penguins, toucans, and raptors, have observed that acupuncture can normalize appetite and digestion, modulate the immune system function, treat musculoskeletal and neurological diseases, and reduce behavior problems [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%